Characteristic of spermogram parameters in men with reproductive pathology in age-related aspect - S. V. Pichugova; V. A. Chereshnev; Ya. B. Beikin (Акушерство, гинекология и репродукция, 2022)
Introduction. The prevalence of andrological diseases among adolescents and young adults resulting in lowered reproductive potential has been noted to progressively increase. At the same time, the number of couples starting to manage reproductive issues after 35–40 years of age highlighting the onset of male androgen deficiency continues to rise. Therefore, the analysis of spermogram as the key element in assessing male reproductive potential is better to conduct at different age periods of man's life.Aim: to compare spermogram parameters in different age groups of patients with reproductive pathology.Materials and Мethods. The analysis of spermograms in adolescents with left-sided grade II–III varicocele aged 17 years and in infertile males aged 22–48 years was performed. Semen analysis was conducted in accordance with the standards of the 5 th edition of the World Health Organization and included the following parameters: semen volume (ml), sperm concentration (million/ml), total sperm count (million), acidity, viscosity, progressive motility, total motility, viability, morphology, detected mucus, leukocytes, amyloid bodies, lecithin grains as well as sperm aggregation and agglutination. The stained preparations were used to assess the morphology of spermatozoa and spermatogenesis cells. According to the spermogram data obtained, the following conclusions were drawn: normozoospermia, oligozoospermia, asthenozoospermia, teratozoospermia. Statistical analysis was performed by using Statistica 10.0 software (StatSoft Inc., USA). The normality distribution was assessed using the χ2 test. Quantitative parameters were presented as arithmetic means and standard deviations (M ± SD). Assessing significance of differences was performed by using the Student's t-test, whereas inter-parameter correlation relations were analyzed by using the linear Pearson's correlation coefficient. A significance level between inter-group parameters was set at p < 0.05.Results. It was found that adolescents with varicocele vs. adult men had significantly decreased ejaculate volume. In particular, the average ejaculate volume in adolescents and adult men was 2.32 ± 1.22 ml and 3.50 ± 1.44 ml, respectively, so that the larger number of young patients were noted to have ejaculate volume below 1.5 ml. Compared to young subjects, aged patients had decreased sperm concentration (35.88 ± 25.74 versus 72.20 ± 49.32 million/ml) and total sperm count (120.58 ± 91.72 versus 173.07 ± 163.92 million). Young patients were found to have significantly superior data in all categories of sperm motility, whereas infertile men were diagnosed with impaired sperm motility. In particular, adolescents were featured with the average number of spermatozoa displaying fast and slow translational movement comprising 17.12 ± 11.04 % and 29.30 ± 12.29 %, respectively, the proportion of progressive motility spermatozoa was 46.20 ± 19.82 %. In contrast, similar parameters in adult men were 5.10 ± 6.36 %, 19.80 ± 9.61 %, and 24.95 ± 11.23 %, respectively. In infertile men prevalence of lacked spermatozoa with rapid forward movement was 46 (46.0 %), in adolescents – 8 (8.6%), whereas rate of immotile spermatozoa in infertile men, on average, accounted for 53.10 ± 14.56 %, in adolescents – 34.40 ± 21.83 %. In addition, adolescents with varicocele had significantly fewer spermatozoa with normal morphology – 14.14 ± 8.06 % (in adult men – 30.08 ± 17.94 %), there were more abundant defects in the sperm head – 58.01 ± 12.43 % (in men – 48.83 ± 18.95 %) and flagella – 17.24 ± 6.31 % (in men – 10.29 ± 6.21 %). The data obtained showed that adolescents were more often diagnosed with normozoospermia – in 49 (52.7 %) cases, in infertile men – in 12 (12.0 %) cases, whereas in aged men asthenozoospermia was detected in 82 (82.0 %) cases, in adolescents – 5 (5.4 %) cases.Conclusion. The abnormalities in the spermogram revealed in adolescents may be associated with unestablished spermatogenesis. Normozoospermia more common in adolescents with varicocele may evidence about preserved reproductive potential. Impaired sperm motility in aged patients seems to be related to the formation of oxidative stress and damage to spermatozoa by reactive oxygen species due to combined age-related changes, cumulation of the negative effects of environmental and lifestyle factors, as well as comorbidities.